Cardiac Fibrosis: Key Role of Integrins in Cardiac Homeostasis and Remodeling - Patrick B. Meagher; Xavier Alexander Lee; Joseph Lee; Aylin Visram; Mark K. Friedberg; Kim A. Connelly (Cells, 2021)
Cardiac fibrosis is a common finding that is associated with the progression of heart failure (HF) and impacts all chambers of the heart. Despite intense research, the treatment of HF has primarily focused upon strategies to prevent cardiomyocyte remodeling, and there are no targeted antifibrotic strategies available to reverse cardiac fibrosis. Cardiac fibrosis is defined as an accumulation of extracellular matrix (ECM) proteins which stiffen the myocardium resulting in the deterioration cardiac function. This occurs in response to a wide range of mechanical and biochemical signals. Integrins are transmembrane cell adhesion receptors, that integrate signaling between cardiac fibroblasts and cardiomyocytes with the ECM by the communication of mechanical stress signals. Integrins play an important role in the development of pathological ECM deposition. This review will discuss the role of integrins in mechano-transduced cardiac fibrosis in response to disease throughout the myocardium. This review will also demonstrate the important role of integrins as both initiators of the fibrotic response, and modulators of fibrosis through their effect on cardiac fibroblast physiology across the various heart chambers.